Respuesta :

Note: Maybe you either forgot to mention the slope or forgot to mention another point from which the equation of the line passes.

In the later part, I would assume the slope m = 2 as an example.

Answer:

Please check the explanation.

Step-by-step explanation:

Given

  • The point (-4, -2)

The point-slope form:

The point-slope form of the line equation is defined as

[tex]y-y_1=m\left(x-x_1\right)[/tex]

where

  • m is the slope of the line
  • (x₁, y₁) is the point

In our case:

(x₁, y₁) = (-4, -2)

substituting the point (-4, -2) in the point-slope form of the equation of the line

[tex]y-y_1=m\left(x-x_1\right)[/tex]

[tex]y-\left(-2\right)=m\left(x-\left(-4\right)\right)[/tex]

Therefore,  the point-slope form of the equation of the line using the point (-4,-2) will be:

  • [tex]y-\left(-2\right)=m\left(x-\left(-4\right)\right)[/tex]

BONUS!

Example Solving with assuming the slope m = 2

Let suppose the slope m = 2

As we have already got the equation in the point-slope form

[tex]y-\left(-2\right)=m\left(x-\left(-4\right)\right)[/tex]

substituting m = 2

[tex]y-\left(-2\right)=2\left(x-\left(-4\right)\right)[/tex]

[tex]y+2=2\left(x+4\right)[/tex]

Subtract 2 from both sides

[tex]y+2-2=2\left(x+4\right)-2[/tex]

[tex]y=2x+6[/tex]

Thus, the point-slope form of the equation of the line using the point (-4,-2) and having slope m = 2.

Answer:

sheesh

Step-by-step explanation: